Pengaruh Resiko Kredit, Resiko Likuiditas, Efisiensi Manajemen terhadap Profitabilitas: Studi pada Perbankan yang Terdaftar di Bursa Efek Indonesia - Chairul Adhim (Center of Language and Cultural Studies, 2019)
This study aims to determine the effect of credit risk, liquidity risk, management efficiency to profitability in Banking listed on the Indonesia Stock Exchange in the period 2010-2014. This research is explanatory research. The population of this study is a banking company listed on the Indonesia Stock Exchange using a saturated sampling technique, obtained a population of 26 banks. Analyzer using regression analysis. The result of the analysis shows that Credit risk and management efficiency have a negative and significant effect on profitability and liquidity risk have no effect on profitability, while the capital has a positive and significant effect on profitability.